SARS-CoV-2 Seroprevalence Compared with Confirmed COVID-19 Cases among Children, Colorado, USA, May–July 2021 - Shannon C. O’Brien; Lyndsey D. Cole; Bernadette A. Albanese; Allison Mahon; Vijaya Knight; Nathan Williams; Rachel Severson; Alexis Burakoff; Nisha B. Alden; Samuel R. Dominguez (Emerging Infectious Diseases, 2023)
To compare SARS-CoV-2 antibody seroprevalence among children with seropositive confirmed COVID-19 case counts (case ascertainment by molecular amplification) in Colorado, USA, we conducted a cross-sectional serosurvey during May–July 2021. For a convenience sample of 829 Colorado children, SARS-CoV-2 seroprevalence was 36.7%, compared with prevalence of 6.5% according to individually matched COVID-19 test results reported to public health. Compared with non-Hispanic White children, seroprevalence was higher among Hispanic, non-Hispanic Black, and non-Hispanic other race children, and case ascertainment was significantly lower among Hispanic and non-Hispanic Black children. This serosurvey accurately estimated SARS-CoV-2 prevalence among children compared with confirmed COVID-19 case counts and revealed substantial racial/ethnic disparities in infections and case ascertainment. Continued efforts to address racial and ethnic differences in disease burden and to overcome potential barriers to case ascertainment, including access to testing, may help mitigate these ongoing disparities.